2009
DOI: 10.1089/neu.2008.0748
|View full text |Cite
|
Sign up to set email alerts
|

Blast Overpressure in Rats: Recreating a Battlefield Injury in the Laboratory

Abstract: Blast injury to the brain is the predominant cause of neurotrauma in current military conflicts, and its etiology is largely undefined. Using a compression-driven shock tube to simulate blast effects, we assessed the physiological, neuropathological, and neurobehavioral consequences of airblast exposure, and also evaluated the effect of a Kevlar protective vest on acute mortality in rats and on the occurrence of traumatic brain injury (TBI) in those that survived. This approach provides survivable blast condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
290
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(309 citation statements)
references
References 30 publications
14
290
5
Order By: Relevance
“…Groups of isoflurane (4%) anesthetized animals (n = 6 for sham and n = 6 for blast) were exposed to repeated blast exposures (20.6 psi), as reported previously, using a shock tube [9,36,[38][39]. At a 6 h time point after the last blast exposure, three animals each from sham and blast groups were euthanized, and the brain tissue was collected after necropsy and separated into various regions as described earlier [39].…”
Section: Animal Blast Exposure Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups of isoflurane (4%) anesthetized animals (n = 6 for sham and n = 6 for blast) were exposed to repeated blast exposures (20.6 psi), as reported previously, using a shock tube [9,36,[38][39]. At a 6 h time point after the last blast exposure, three animals each from sham and blast groups were euthanized, and the brain tissue was collected after necropsy and separated into various regions as described earlier [39].…”
Section: Animal Blast Exposure Modelmentioning
confidence: 99%
“…Auditory/vestibular injuries from blast traumatic brain injury (TBI) can cause increased incidence of tinnitus and hearing loss, which worsens over time if not treated [1][2][3][4]. Shock waves generated from explosive blasts are reported to be destructive to both gas-and fluid-filled structures of the body, including the lungs, intestines, brain, eyes, nose, and middle ear [5][6][7][8][9]. Blast-induced damage to the auditory system can be the consequence of either direct exposure of the auditory canal to blast shock waves or TBI and impairment in the central auditory processing involving different brain regions after blast exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most widely employed version is the shock tube utilized by researchers at the Walter Reed Institute for Army Research/Naval Medical Research Center [27][28][29][30]. A 30 cm diameter, 5.33 m long galvanized steel tube is attached to a smaller pipe of the same diameter.…”
Section: B Blast Overpressure Shock Tubesmentioning
confidence: 99%
“…Intracranial measures in anesthetized rats demonstrated overpressure within the cerebral ventricles in the range of 30-40 kPa [31], and that blast effects upon intracranial pressure persisted for hours after exposure [24]. Long [28] reports that shock tube exposure at relatively higher levels (126-147 kPa) leads to cerebral hemorrhage, necrosis, cortical cell loss, gliosis, and widespread fiber degeneration, which is not reported in many studies with fluid percussion or control cortical impact injury; others also have reported little evidence of obvious focal cortical injury [25,31]. Compared to the methods described in A-C, the shock tube permits whole-body exposure, which is relevant to body effects from blast on neurological function, and studies related to the impact of armor or protective clothing are feasible [25,28].…”
Section: B Blast Overpressure Shock Tubesmentioning
confidence: 99%
See 1 more Smart Citation